The Effect of Problem-Based Learning on Students’ Science Literacy Skills on the Topic of Human Excretory System - Ajeng Fajar Ramadhanti; Suharsono Suharsono; Egi Nuryadin (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
Science literacy is one of the 21st-century skills that students need to have. One of the things that affects students' science literacy skills is the learning model used. This study aims to determine the effect of the Problem-Based Learning (PBL) learning model on students' science literacy skills in human excretory system material in the class XI MIPA SMA Negeri 1 Tasikmalaya, Academic Year 2022/2023. The research method used was a quasi-experiment with a static-group comparison design. The population in this study were all XI MIPA classes of SMA Negeri 1 Tasikmalaya as many as 8 classes with a total of 283 students. The sampling technique was done by cluster random sampling method. The sample used in this study consisted of 2 classes, namely class XI MIPA 2 as an experimental class with a total of 33 students and class XI MIPA 3 as a control class with a total of 39 students. Data collection techniques in the form of giving instruments of science literacy skills with multiple choice questions as many as 37 questions related to the topic of human excretory system. Hypothesis testing using an independent t-test with a Sig value. (2-tailed) of 0.000 <0.05, therefore that H0 is rejected means that there is an effect of Problem-Based Learning (PBL) on students' science literacy skills on the subject of human excretory system in class XI MIPA SMA Negeri 1 Tasikmalaya Academic Year 2022/2023.